1999
DOI: 10.1074/jbc.274.11.7583
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosines in the Bidentate Motif of the env-sea Oncoprotein Are Essential for Cell Transformation and Are Binding Sites for Grb2 and the Tyrosine Phosphatase SHP-2

Abstract: The transforming gene product of the S13 avian erythroblastosis virus, the env-sea protein, is a member of the hepatocyte growth factor receptor family of tyrosine kinases comprising Met, Ron, and Sea. Like all three members of this family, the env-sea protein has a socalled bidentate motif (Y 557 INMAVTY 564 VNL) composed of two tandemly arranged tyrosines in the carboxyl terminus. To investigate whether the tyrosine residues in this motif are essential for the env-sea-mediated transformation, we generated ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…All Gab family members contain multiple p85-binding sites that become phosphorylated upon receptor activation (Liu and Rohrschneider, 2002), and we demonstrate here that the p85-binding sites in Gab2 are required for efficient cytokine-independent growth of Friend virus-infected erythroblasts. The ability of Gab proteins to amplify Sf-Stk signaling through the activation of PI3K is consistent with previous findings from our laboratory that demonstrate a requirement for PI3K activation in the transformation of cells by FV (Park and Hayman, 1999;Finkelstein et al, 2002). Our data also extend previous studies demonstrating constitutive tyrosine phosphorylation of Gab2 and its association with p85 in FV-infected cells grown in the absence of Epo (Lecoq-Lafon et al, 1999;Wickrema et al, 1999;Nishigaki et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All Gab family members contain multiple p85-binding sites that become phosphorylated upon receptor activation (Liu and Rohrschneider, 2002), and we demonstrate here that the p85-binding sites in Gab2 are required for efficient cytokine-independent growth of Friend virus-infected erythroblasts. The ability of Gab proteins to amplify Sf-Stk signaling through the activation of PI3K is consistent with previous findings from our laboratory that demonstrate a requirement for PI3K activation in the transformation of cells by FV (Park and Hayman, 1999;Finkelstein et al, 2002). Our data also extend previous studies demonstrating constitutive tyrosine phosphorylation of Gab2 and its association with p85 in FV-infected cells grown in the absence of Epo (Lecoq-Lafon et al, 1999;Wickrema et al, 1999;Nishigaki et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In these cells, PI3K is constitutively active, and PI3K activity, but not EpoR phosphorylation, is required for the proliferation of these cells in the absence of Epo (Nishigaki et al, 2000). Furthermore, v-sea, which induces erythroleukemia in chickens, preferentially interacts with Gab2 and is essential for cellular transformation induced by v-sea (Ischenko et al, 2003), and mutagenesis studies revealed a critical role in v-sea-induced transformation for PI3K activation (Park and Hayman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of these two tyrosines (Y1353F/Y1360F) suppressed the transforming ability of activated forms of RON (15). A similar mutation caused a complete loss of transforming ability of the related SEA kinase (22). These results could be the result of the inability of the double mutant to engage SH2 domain-containing downstream signaling proteins.…”
mentioning
confidence: 79%
“…Two tyrosine residues within the carboxyl terminus of Met (Y1349 and Y1356), which are highly conserved between the other members of the Met receptor tyrosine kinase gene family, Sea and Ron, are crucial for cell scatter and epithelial morphogenesis in Madin-Darby canine kidney (MDCK) epithelial cells (29,48,58,74,83). Y1356 forms a multisubstrate-binding site, coupling the Met receptor with the Grb2 and Shc adapter proteins, as well as the Cbl proto-oncogene and the Grb2-associated binder 1 (Gab1) (10-12, 44, 51, 73).…”
mentioning
confidence: 99%